Enhanced paraben removal through synergistic catalytic ozonation and adsorption processes using Fe3O4-GAC magnetic composite - Bahareh Ahmadi; Abooalfazl Azhdarpoor; Mohammad Hoseini (Applied Water Science)
Abstract The potential long-term deleterious effects of parabens on ecosystems, particularly as endocrine disruptors, have been a source of concern due to their persistent presence in natural waters. This study evaluated the catalytic performance of Fe3O4-enhanced granular activated carbon (Fe3O4-GAC) in the catalytic ozonation of methyl-paraben (MP) and ethyl-paraben (EP). Characterization confirmed that Fe3O4 nanoparticle improved GAC’s surface properties, enhancing reaction efficiency. Under optimized conditions (1.5 g/L GAC, pH 3, 20 mg/L parabens, 45 min), the adsorption process achieved removal efficiencies of 70% for MP and 65% for EP. Fe3O4-GAC outperformed ozonation and catalytic ozonation with GAC, removing 98% of MP and 95% of EP at pH 9, 1 g/L catalyst, and 5 min of reaction time. Adsorption kinetics followed the pseudo-first-order kinetic model with higher determination coefficients (R2: 0.9369 for MP, 0.9164 for EP) than the pseudo-second-order model, while the Langmuir isotherm best described the process (R2: 0.9782 for MP, 0.9933 for EP). Degradation in catalytic ozonation using Fe3O4-GAC also followed the pseudo-first-order kinetic model, achieving rate constants of 0.4437 min⁻1 for MP and 0.3076 min⁻1 for EP. Moreover, the catalyst demonstrated excellent reusability, maintaining high performance after five successive cycles. These findings underline the potential of Fe3O4-GAC as a sustainable and efficient catalyst for removing parabens from water, addressing an urgent environmental challenge.